2021
DOI: 10.1108/sef-02-2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

Early COVID-19 policy response on healthcare equity prices

Abstract: Purpose This paper aims to investigate the implementation of the short selling ban policy imposed by the Italian stock exchange on health-care stock prices, as a tool to mitigate COVID-19 price effects. Important contributions are in terms of assessing the effect of the temporary short selling ban on restricted health-care stocks; the effect of COVID-19 cases and crude oil price volatility onto health-care stocks; and whether COVID-19 resulted in a change in the risk and average stock price of health-care stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Therefore, fluctuations in oil price can have a direct impact on the cost of production and company profitability. For example, while Gurrib (2021) and Prabheesh et al (2020) recently found that shocks to the number of crude oil price volatility impacted stocks during early COVID-19, Gurrib (2018), Gurrib (2019); and Lescaroux and Mignon (2008) find crude oil prices to be poor predictors in other markets. This is in line with Kinateder et al (2021) who compared correlations across different asset classes and found deteriorating relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fluctuations in oil price can have a direct impact on the cost of production and company profitability. For example, while Gurrib (2021) and Prabheesh et al (2020) recently found that shocks to the number of crude oil price volatility impacted stocks during early COVID-19, Gurrib (2018), Gurrib (2019); and Lescaroux and Mignon (2008) find crude oil prices to be poor predictors in other markets. This is in line with Kinateder et al (2021) who compared correlations across different asset classes and found deteriorating relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the short run, new COVID‐19 death cases have a positive impact on the Refinitiv Global Healthcare Price Return Index and the Refinitiv Global Pharmaceuticals & Medical Research Price Return Index, as argued by Gurrib ( 2021 ); Harjoto and Rossi ( 2021 ); He et al ( 2020 ); Mazur et al ( 2021 ); Mushafiq ( 2021 ). Likewise, according to Alam et al ( 2021 ), the positive influence is asserted by rising demand for medical devices and pharmaceutics.…”
Section: Empirical Findingsmentioning
confidence: 95%
“…This impact is similar in various countries where governments ordered businesses to shut and families to stay at home except for essential activities. Shehzad et al (2020) find the conditional variance of stock markets to be bigger during the COVID-19 compared to the global financial crisis of -2008. Gurrib (2021 similarly find shocks to the number of COVID-19 cases affected healthcare sector companies but lasted only a few days.…”
Section: Introductionmentioning
confidence: 94%